A nylon composition, its preparation and use

CN122898129APending Publication Date: 2026-10-13SHENZHEN XINPENGYU NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611020356.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但涂层在长期使用和反复清洗后存在耐久性问题;(2)塑料改性技术,工艺简单易行,适用于现有生产线,但功能性单体的添加比例也受限于聚合反应的稳定性和产物性能;(3)使用深色材料作为厨具材料,但这限制了产品设计的多样性

Benefits of technology

[0009]本发明一种实施方式的尼龙组合物,该尼龙组合物能够使相应的尼龙材料具有更佳的品质,例如更好的耐染色、更高的强度等。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a kind of nylon composition and its preparation method and application, and the nylon composition includes nylon 66, polytetrafluoroethylene, glass fiber and additive;Wherein, the additive includes mineral powder, compatilizer, lubricant, anti-aging agent and flow modifier, the nylon composition can make corresponding nylon material have better quality, such as better dyeing resistance, higher strength etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a nylon composition, and more particularly to a nylon composition that can be used to manufacture stain-resistant kitchenware. Background Technology

[0002] Nylon (polyamide, PA) is widely used in kitchenware manufacturing due to its excellent heat resistance, abrasion resistance, and processing properties. However, nylon materials themselves have a certain affinity for organic pigments, especially light-colored products, which are prone to adsorbing pigment molecules such as curcumin added to mustard sauce during use, resulting in surface staining.

[0003] Studies have shown that the staining mechanism of mustard on nylon products includes three aspects: (1) chemical adsorption: allyl isothiocyanate (AITC) in mustard has high reactivity and can undergo nucleophilic addition reaction with amide bonds in nylon molecular chains to generate thiourea derivatives and form strong chemical bonds; (2) physical adsorption: lipophilic components such as curcumin are adsorbed onto the nylon surface through van der Waals forces and hydrophobic interactions; (3) permeation diffusion: moisture causes nylon to swell, allowing dye molecules to further penetrate into the material. These three mechanisms together make it difficult to remove mustard staining.

[0004] Existing solutions mainly include: (1) forming a physical barrier through surface coating treatment. However, the coating has durability issues after long-term use and repeated cleaning; (2) plastic modification technology, which is simple and easy to implement and suitable for existing production lines, but the proportion of functional monomers added is also limited by the stability of the polymerization reaction and the performance of the product; (3) using dark-colored materials as kitchenware materials, but this limits the diversity of product design.

[0005] In summary, there is currently a lack of a mature technical solution that can effectively solve the problem of dyeing light-colored nylon mustard sauce from the perspective of material bulk modification, while taking into account both processing performance and performance. Summary of the Invention

[0006] To overcome at least one of the defects of the prior art, in a first aspect, one embodiment of the present invention provides a nylon composition comprising nylon 66, polytetrafluoroethylene, glass fiber, and additives; wherein the additives include mineral powder, compatibilizer, lubricant, anti-aging agent, and flow modifier.

[0007] Secondly, one embodiment of the present invention provides a nylon material, which is obtained by extruding the components of the above-described nylon composition after mixing them.

[0008] Thirdly, one embodiment of the present invention provides a kitchen utensil comprising a nylon material made from the above-described nylon composition or the above-described nylon material.

[0009] The present invention provides a nylon composition that enables the corresponding nylon material to have better qualities, such as better dye resistance and higher strength. Detailed Implementation

[0010] Typical embodiments embodying the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various variations in different embodiments without departing from the scope of the present invention, and the description herein is for illustrative purposes only and not intended to limit the present invention.

[0011] One embodiment of the present invention provides a nylon composition comprising nylon 66, polytetrafluoroethylene, glass fiber, and additives; wherein the additives include mineral powder, compatibilizer, lubricant, anti-aging agent, and flow modifier.

[0012] In one embodiment, the nylon composition comprises 100 parts by weight of nylon 66, 10-20 parts by weight of polytetrafluoroethylene, 70-85 parts by weight of glass fiber, 10-20 parts by weight of mineral powder, 10-20 parts by weight of compatibilizer, 10-20 parts by weight of lubricant, 3-10 parts by weight of anti-aging agent, and 5-15 parts by weight of flow modifier.

[0013] In one embodiment, the nylon composition comprises 100 parts by weight of nylon 66, 10-15 parts by weight of polytetrafluoroethylene, 70-80 parts by weight of glass fiber, 12-18 parts by weight of mineral powder, 12-18 parts by weight of compatibilizer, 10-15 parts by weight of lubricant, 6-10 parts by weight of anti-aging agent, and 5-10 parts by weight of flow modifier.

[0014] In one embodiment, the amount of nylon 66 is 100 parts by weight, and the amount of polytetrafluoroethylene can be 10 to 20 parts by weight, or more specifically 10 to 15 parts by weight, for example 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, or 15 parts by weight.

[0015] In one embodiment, the amount of nylon 66 is 100 parts by weight, and the amount of mineral powder can be 10 to 20 parts by weight, or more specifically 12 to 18 parts by weight, for example 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, or 18 parts by weight.

[0016] In one embodiment, the amount of nylon 66 is 100 parts by weight, and the amount of glass fiber can be 70 to 85 parts by weight, or more specifically 70 to 80 parts by weight, for example 71 parts by weight, 72 parts by weight, 73 parts by weight, 74 parts by weight, 75 parts by weight, 76 parts by weight, 77 parts by weight, 78 parts by weight, 79 parts by weight, or 80 parts by weight.

[0017] In one embodiment, the amount of nylon 66 is 100 parts by weight, and the amount of compatibilizer can be 10 to 20 parts by weight, or more specifically 12 to 18 parts by weight, for example 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, or 18 parts by weight.

[0018] In one embodiment, the amount of nylon 66 is 100 parts by weight, and the amount of lubricant can be 10 to 20 parts by weight, or more specifically 10 to 15 parts by weight, for example 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, or 15 parts by weight.

[0019] In one embodiment, the amount of nylon 66 is 100 parts by weight, and the amount of anti-aging agent can be 3 to 10 parts by weight, or more specifically 6 to 10 parts by weight, for example 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, or 10 parts by weight.

[0020] In one embodiment, the amount of nylon 66 is 100 parts by mass, and the amount of flow modifier can be 5 to 15 parts by mass, or more specifically 5 to 10 parts by mass, for example 5 parts by mass, 6 parts by mass, 7 parts by mass, 8 parts by mass, 9 parts by mass, or 10 parts by mass.

[0021] In one embodiment, the mineral powder includes one, two or more of talc, calcium carbonate, and barium sulfate.

[0022] In one embodiment, the compatibilizer includes one, two, or more of maleic anhydride-grafted, ethylene copolymer-type, and isocyanate-type compatibilizers.

[0023] In one embodiment, the lubricant includes one, two, or more of silicone powder, EBS, TAF, stearate, and polyethylene wax.

[0024] In one embodiment, the flow modifier includes one, two, or more of dendritic polymers, hyperbranched polymers, and polybasic acid copolymers.

[0025] In one embodiment, the anti-aging agent includes one, two, or more of hindered phenols, phosphites, and hindered amines.

[0026] In one embodiment, the glass fiber is alkali-free glass fiber (alkali-free glass fiber) with a diameter of 9 to 15 micrometers, or more specifically 10 to 13 micrometers, for example, 9 micrometers, 10 micrometers, 11 micrometers, or 13 micrometers.

[0027] One embodiment of the present invention provides a nylon material, which is obtained by extruding the components of the above-described nylon composition after mixing them.

[0028] In one embodiment, the tensile strength of the nylon material is 170~200MPa, preferably 180~200MPa, such as 175MPa, 180MPa, 185MPa, 190MPa, 195MPa, etc.

[0029] In one embodiment, the elongation at break of the nylon material is 2 to 4%, preferably 2.5 to 4%, for example 3%, 3.5%, etc.

[0030] In one embodiment, the flexural strength of the nylon material is 260-290 MPa, preferably 270-290 MPa, such as 265 MPa, 270 MPa, 275 MPa, 280 MPa, 285 MPa, etc.

[0031] In one embodiment, the flexural modulus of the nylon material is 8000-10000 MPa, preferably 8000-9000 MPa, such as 8500 MPa, 9000 MPa, 9500 MPa, etc.

[0032] In one embodiment, the dry-state cantilever beam notched impact strength of the nylon material is 9–13 kJ / m², preferably 10–13 kJ / m², such as 9.5 kJ / m², 10 kJ / m², 10.5 kJ / m², 11 kJ / m², 11.5 kJ / m², 12 kJ / m², 12.5 kJ / m², etc.

[0033] In one embodiment, the heat distortion temperature of the nylon material is 240–260°C, such as 245°C, 250°C, 255°C, etc.

[0034] In one embodiment, the melting temperature (DSC) of the nylon material is 250–270°C, such as 255°C, 260°C, 265°C, etc.

[0035] In one embodiment, the ΔE of the nylon material is 0.4 to 1.4, preferably 0.4 to 1.0, such as 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, etc.

[0036] One embodiment of the present invention provides a method for preparing the above-mentioned nylon material, comprising: mixing the components of the above-mentioned nylon composition and then extruding to obtain the nylon material.

[0037] In one embodiment, the method for preparing nylon material includes a mixing step and an extrusion step.

[0038] In one embodiment, the mixing step includes: Nylon 66, PTFE, mineral powder, compatibilizer, and anti-aging agent are mixed in a mixer for 5-10 minutes to obtain material A; The flow modifier and lubricant are mixed in a mixer for 5–10 minutes to obtain material B; and Mix material A and material B in a mixer for 5 to 10 minutes to obtain material C.

[0039] In one embodiment, the mixer used in the mixing step may be a high-speed mixer (high-speed mixer).

[0040] In one embodiment, the extrusion step includes: adding material C and glass fiber into an extruder for granulation to obtain nylon material.

[0041] In one embodiment, the temperature of the extruder is 200–270°C.

[0042] In one embodiment, the extrusion step includes: adding material C into the main hopper of a twin-screw extruder and feeding it into the extruder through the main feeder; feeding glass fiber into the extruder through the side feeder to granulate it and obtain nylon material.

[0043] In one embodiment, a twin-screw extruder is selected, and the temperatures of each zone are set as follows: zone 1 temperature 200-230℃, zone 2 temperature 250-270℃, zone 3 temperature 250-270℃, zone 4 temperature 250-270℃, zone 5 temperature 250-270℃, zone 6 temperature 250-270℃, zone 7 temperature 250-270℃, zone 8 temperature 250-270℃, zone 9 temperature 250-270℃, and die head temperature 260-280℃; the main extruder speed can be 400-600 r / min.

[0044] One embodiment of the present invention provides a kitchen utensil comprising a nylon material made from the above-described nylon composition or the above-described nylon material.

[0045] In one embodiment, the dried granules are added to an injection molding machine to ensure that the moisture content is less than 0.2%, and then injection molded into kitchenware products according to the following process parameters.

[0046] The injection molding process parameters are as follows: the first stage temperature is set to 260~275℃, the second stage temperature is set to 270~280℃, and the third stage temperature is set to 280~290℃; the melt temperature is set to 270~300℃, and the mold temperature is set to 50~120℃.

[0047] The nylon composition of one embodiment of the present invention enables the corresponding nylon material to have better qualities, such as better stain resistance and higher strength.

[0048] The preparation of a nylon material according to one embodiment of the present invention will be further described below with reference to specific examples. The raw materials and testing methods used in each embodiment are as follows.

[0049] raw material 1. PA66 was purchased from Shenma Nylon; 2. The glass fiber (T435TM) was purchased from Taishan Glass Fiber. 3. Polytetrafluoroethylene (0143) was purchased from Zhongte; 4. Mineral powder (400A) was purchased from Meirun; 5. Compatibilizer (WIC-3) was purchased from KOAS; 6. The lubricant (TAF) was purchased from Borun; 7. The flow modifier (X100) was purchased from Langzhen; 8. Anti-aging agent (770) was purchased from Rianlong.

[0050] Test methods 1. Specific gravity: The specific gravity of the nylon product is measured with reference to standard ISO 1183.

[0051] 2. Melt Flow Index: The melt flow index of nylon products is measured with reference to standard ISO 1133.

[0052] 3. Ash content: The ash content of the nylon product was measured with reference to standard ISO 3451.

[0053] 4. Moisture content: The moisture content of the nylon product was measured with reference to standard ISO 62.

[0054] 5. Tensile strength and elongation at break: The tensile strength and elongation at break of the nylon products were measured in accordance with standard ISO 527.

[0055] 6. Bending strength and bending modulus: The bending strength and bending modulus of the nylon products were measured with reference to standard ISO 178.

[0056] 7. Notched impact strength and unnotched impact strength of cantilever beams: The notched impact strength and unnotched impact strength of cantilever beams of nylon products were measured with reference to standard ISO 180.

[0057] 8. Heat distortion temperature: The heat distortion temperature of nylon products is measured with reference to standard ISO 75.

[0058] 9. Melting temperature DSC: The melting temperature of nylon products is measured with reference to standard ISO 11357.

[0059] 10. Dyeing Test: Before the test, wash the nylon kitchenware with clean water and drain. Select a flat area on the sample surface as the measurement point and record the initial color data of this point using a colorimeter to obtain the L, a, and b values ​​as the baseline values. Evenly spread mustard sauce on the surface and let it stand at room temperature for 4 hours. After the test, wash with clean water by hand and gently wipe with a soft cloth or sponge. Use the same colorimeter to measure the color again at the same measurement point to obtain new L', a', and b' values. The instrument will automatically calculate the color difference between the two measurements; this difference is ΔE (usually written as ΔE). ab).

[0060] The formula for calculating ΔE is: ΔE = √[(ΔL)² + (Δa)² + (Δb)²] Where ΔL, Δa, and Δb represent the changes in brightness, red-green value, and yellow-blue value, respectively; L value: Indicates brightness, ranging from 0 (black) to 100 (white).

[0061] a value: indicates the red-green color tendency, with positive values ​​for red and negative values ​​for green.

[0062] b-value: indicates the yellow-blue hue tendency; a positive value is yellow, and a negative value is blue.

[0063] Finally, the degree of staining is determined based on the value of ΔE to evaluate the stain resistance of nylon cookware. A value of ΔE less than 1.5 indicates no obvious staining change visible to the naked eye, which is considered acceptable; a value of ΔE greater than 1.5 indicates a significant color change.

[0064] 11. Migration test: Refer to Annex II and Annex V of European Commission Regulation (EU) No 10 / 2011 (14 January 2011) for the selection of test conditions, and refer to EN1186-1:2002 for the selection of test methods: EN1186-3:2022 Test method for total migration in volatile simulants.

[0065] Example 1 S1: Add Nylon 66, PTFE, mineral powder, compatibilizer, and anti-aging agent to the high-speed mixer and mix for 10 minutes to obtain material A; add flow modifier and lubricant to the high-speed mixer and mix for 10 minutes to obtain material B; add material A and material B to the high-speed mixer and mix for 10 minutes to obtain material C.

[0066] S2: Add material C to the main hopper of the twin-screw extruder and feed it into the extruder through the main feeder; feed glass fiber into the extruder through the side feeder to granulate and obtain nylon products; The temperature settings for each zone of the twin-screw extruder are as follows: Zone 1: 230℃, Zone 2: 260℃, Zone 3: 260℃, Zone 4: 260℃, Zone 5: 260℃, Zone 6: 260℃, Zone 7: 250℃, Zone 8: 250℃, Zone 9: 250℃; Die head temperature: 270℃; Extruder main unit speed: 530 r / min.

[0067] Nylon products are added to an injection molding machine, the material is melted and extruded, and then shaped through a mold to obtain nylon kitchenware products; The injection molding process parameters are as follows: the first stage temperature is set to 260℃, the second stage temperature is set to 270℃, the third stage temperature is set to 280℃; the melt temperature is set to 270℃; and the mold temperature is set to 80℃.

[0068] Examples 1 to 6 and Comparative Examples 1 to 3 all used the same process as Example 1 to prepare nylon products or nylon kitchenware products. The difference was that the types and amounts of raw materials used were different, as detailed in Table 1.

[0069] Table 1

[0070] The test results of various tests conducted on the nylon products or nylon kitchenware products of Examples 1 to 4 and Comparative Examples 1 to 3 are shown in Table 2.

[0071] Table 2

[0072] Unless otherwise specified, the terms used in this invention have the meanings commonly understood by those skilled in the art.

[0073] The embodiments described in this invention are for illustrative purposes only and are not intended to limit the scope of protection of this invention. Those skilled in the art can make various other substitutions, changes and improvements within the scope of this invention. Therefore, this invention is not limited to the above embodiments, but is only defined by the claims.

Claims

1. A nylon composition comprising nylon 66, polytetrafluoroethylene, glass fiber, and additives; wherein, The additives include mineral powder, compatibilizer, lubricant, anti-aging agent and flow modifier.

2. The nylon composition according to claim 1, comprising 100 parts by weight of the nylon 66, 10-20 parts by weight of polytetrafluoroethylene, 70-85 parts by weight of glass fiber, 10-20 parts by weight of mineral powder, 10-20 parts by weight of compatibilizer, 10-20 parts by weight of lubricant, 3-10 parts by weight of anti-aging agent, and 5-15 parts by weight of flow modifier.

3. The nylon composition according to claim 1, comprising 100 parts by weight of the nylon 66, 10-15 parts by weight of polytetrafluoroethylene, 70-80 parts by weight of glass fiber, 12-18 parts by weight of mineral powder, 12-18 parts by weight of compatibilizer, 10-15 parts by weight of lubricant, 6-10 parts by weight of anti-aging agent, and 5-10 parts by weight of flow modifier.

4. The nylon composition according to claim 1, wherein the compatibilizer comprises one, two, or more of maleic anhydride-grafted, ethylene copolymer-type, and isocyanate-type compatibilizers; and / or, The flow modifier includes one, two or more of organosilicon polymers, hyperbranched polymers, and dendritic polymers.

5. The nylon composition according to claim 1, wherein the lubricant comprises one, two or more of silicone powder, EBS, TAF, stearate, and polyethylene wax; and / or, The glass fiber is alkali-free glass fiber.

6. The nylon composition according to claim 1, wherein the anti-aging agent comprises one, two or more of silicone powder, EBS, TAF, stearate, and polyethylene wax; and / or, The glass fiber has a diameter of 9 to 15 micrometers.

7. A nylon material, obtained by extruding the components of the nylon composition according to any one of claims 1 to 6.

8. The nylon material according to claim 7, wherein the tensile strength of the nylon material is 170~200 MPa; and / or, The elongation at break of the nylon material is 2-4%, preferably 2.5-4%; and / or, The flexural strength of the nylon material is 260–290 MPa, preferably 270–290 MPa; and / or, The flexural modulus of the nylon material is 8000–10000 MPa, preferably 8000–9000 MPa; and / or, The dry-state cantilever beam notched impact strength of the nylon material is 9–13 kJ / m², preferably 10–13 kJ / m².

9. The nylon material according to claim 7, wherein the heat distortion temperature of the nylon material is 240–260°C; and / or, The melting temperature (DSC) of the nylon material is 250–270°C; and / or, The ΔE of the nylon material is 0.4~1.4, preferably 0.4~1.

0.

10. A kitchen utensil comprising a nylon material made from the nylon composition of any one of claims 1 to 6 or the nylon material of claims 7 to 9.